2013
DOI: 10.1037/lhb0000008
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the association between psychopathy and dissimulation using the MMPI-2-RF validity scales.

Abstract: This investigation sought to determine whether individuals high on psychopathic traits are better able than those low on such traits to avoid detection when feigning psychopathology in the context of a forensic psychological evaluation. Study 1 tested whether individuals high on psychopathy were better able than those low on psychopathy to avoid detection by the Minnesota Multiphasic Personality Inventory 2-Restructured Form's (MMPI-2-RF; Ben-Porath, Y. S., & Tellegen, A., 2008, Minnesota Multiphasic Personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 57 publications
5
44
0
Order By: Relevance
“…However, in practice this is often not the case; an assessment of psychopathy can have long-term implications for the offender. Marion et al (2012) found that psychopathic individuals were no better at avoiding detection of malingering compared to non-psychopathic individuals when completing self-report measures. This may add weight to the use of self-report measures; however, they argue for inclusion of a test of response bias like the PPI, which currently the TriPM lacks.…”
Section: Clinical Applicationmentioning
confidence: 85%
See 3 more Smart Citations
“…However, in practice this is often not the case; an assessment of psychopathy can have long-term implications for the offender. Marion et al (2012) found that psychopathic individuals were no better at avoiding detection of malingering compared to non-psychopathic individuals when completing self-report measures. This may add weight to the use of self-report measures; however, they argue for inclusion of a test of response bias like the PPI, which currently the TriPM lacks.…”
Section: Clinical Applicationmentioning
confidence: 85%
“…These issues aside, initial support for the TriPM's content validity can be drawn from the findings for concurrent validity (described above) in studies such as Marion et al (2012) and Stanley, Wygant and Sellbom (2013). They highlight how the TriPM scales are related to other measures of psychopathy relevant traits.…”
Section: Discriminant Validitymentioning
confidence: 95%
See 2 more Smart Citations
“…Patrick (2010) developed the Triarchic Psychopathy Measure (TriPM) to directly assess the triarchic domains. Subsequent to its release, several studies had reported evidence supporting the convergent and discriminant validity of the three scale scores in undergraduate Marion et al, 2013;Sellbom & Phillips, 2013), community (Anderson, Sellbom, Wygant, Salekin, & Krueger, in press;Strickland, Drislane, Lucy, Krueger, & Patrick, 2013), and correctional (Patrick, 2010;Sellbom & Phillips, 2013;Stanley, Wygant, & Sellbom, 2013) samples based on their absolute and relative associations with a broad range of other psychopathy measures and conceptually relevant personality traits.…”
mentioning
confidence: 99%